Investigation of abundant treated sea sand with different percentages in concrete brick making ratio 1:6 - Wan Munir Najmi, Wan Ab Aziz (2010)
These studies present the result of flexural strength and shrinkage for evaluating the abundant sea sand brick. Flexural strength and shrinkage of abundant sea sand brick according the requirement British Standard 6073- 1 1981. The optimum mix proportion by percentage of the abundant sea sand which is 5%, 10%, 15%, 20%. Result of the test indicated that the proportion abundant sea sand and mix design were the two key factors the quality of brick. Increasing the percentage sea sand in brick significantly reduce the strength the concrete brick. The rate of strength gain of the continuously cured the sample beyond 28 days was also found to be significantly. A weakness in abundant sea sand brick was shown during the flexural experiment. This paper presents the role of different percentage in the cement brick that came as a result of our survey to their effect. The material used are cheap and it consider and waste material. For this purpose 200 brick sample include abundant sea sand brick were design for a particular strength and application building works. The trial mix and abundant sea sand was used are 1:6 for sand cement ratio. The water cement ratio use for this experiment was 0.4. The mould sizes were used 205mm x 150mm x 65mm. The flexural strength and shrinkage wastested at 7, and 28 days of water curing. Based on the result obtained, conclusion can made which is the appropriate percentage of abundant sea sand brick for producing quality cement brick was in the range 5% to 15%.